2014
DOI: 10.1080/15299732.2013.844218
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Depression Among Women with Fibromyalgia or Rheumatoid Arthritis

Abstract: The aim of this study was to inquire about the possible relations of childhood trauma, anger, and dissociation to depression among women with fibromyalgia or rheumatoid arthritis. Fifty female patients diagnosed as having fibromyalgia (n = 30) or rheumatoid arthritis (n = 20) participated in the study. The Childhood Trauma Questionnaire, Somatoform Dissociation Questionnaire (SDQ), Dissociation Questionnaire (DIS-Q), Beck Depression Inventory (BDI), Spielberger State-Trait Anger Expression Inventory, and Disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
3
25
1
Order By: Relevance
“…Our findings are similar to other studies and support the claim that CTs may predispose to FM disease. Because of the variety of literature on trauma subtype, it is difficult to define a specific subscale score related with FM (12,15,(33)(34)(35). Similar to the study of Taylor et al (36), there was no difference in sexual abuse subscale of trauma between study and control groups in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings are similar to other studies and support the claim that CTs may predispose to FM disease. Because of the variety of literature on trauma subtype, it is difficult to define a specific subscale score related with FM (12,15,(33)(34)(35). Similar to the study of Taylor et al (36), there was no difference in sexual abuse subscale of trauma between study and control groups in our study.…”
Section: Discussionsupporting
confidence: 73%
“…An epidemiological study conducted in a town of central-eastern Turkey reported that this type of depressive disorder constituted 40% of the depression cases among women in the community [57]. A recent study on women with fibromyalgia or rheumatoid arthritis revealed that there was a relationship between childhood trauma, posttraumatic anger, dissociation and major depression [58]. Interestingly, in the present study, both depression and dissociation were associated with cumulative trauma of adulthood rather than those of childhood.…”
Section: Discussionmentioning
confidence: 59%
“…A different appearance was obtained in a study (Kiliç et al, 2014) of women with a physical illness which explored the relationship of post-traumatic anger and cognitive-emotional and sensori-motor dissociation to unipolar depression. The diagnosis of lifetime depressive disorder (a trait measure) was predicted by sensori-motor dissociation whereas cognitive-emotional dissociation was related to current severity of depression (a state measure).…”
Section: Embodied Trauma and Bodily Dissociation: Clinical Implicationsmentioning
confidence: 99%